1980
DOI: 10.1002/jnr.490050505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of morphine on sensory‐evoked responses recorded from central gray, reticular formation, thalamus, hypothalamus, limbic system, basal ganglia, dorsal raphe, locus ceruleus, and pineal body

Abstract: Field potential recordings of acoustic and photic-evoked responses were obtained from 15 brain sites of freely behaving unanesthetized rats previously implanted stereotaxically with permanent electrodes. Several dosages of morphine (1, 5, 10, 30, and 50 mg/kg) were examined. The activities recorded from all the structures in this study, except the cochlear nucleus (CoN), were affected by morphine. Different sensitivities to morphine threshold were observed between structures, and several structures exhibited d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…The effects of morphine on BOLD signal intensity correspond well with the described localisation of μ-opioid receptors in the CNS (Mansour et al 1987) and their functional effect on behavioural and neuronal responses (Dafny et al 1980;Presley et al 1990;Hill et al 1982;Lewis and Gebhart 1977;Manning and Mayer 1995;Yeung et al 1977) and on cerebral glucose metabolism (Cohen et al 1991). Our rat data are in keeping with human fMRI imaging studies demonstrating opioid receptor-mediated modulation of activity in cortical brain areas (Borras et al 2004;Petrovic et al 2002) and the nucleus accumbens (Borras et al 2004).…”
Section: Morphine-evoked Changes In Bold Signal Intensitysupporting
confidence: 57%
“…The effects of morphine on BOLD signal intensity correspond well with the described localisation of μ-opioid receptors in the CNS (Mansour et al 1987) and their functional effect on behavioural and neuronal responses (Dafny et al 1980;Presley et al 1990;Hill et al 1982;Lewis and Gebhart 1977;Manning and Mayer 1995;Yeung et al 1977) and on cerebral glucose metabolism (Cohen et al 1991). Our rat data are in keeping with human fMRI imaging studies demonstrating opioid receptor-mediated modulation of activity in cortical brain areas (Borras et al 2004;Petrovic et al 2002) and the nucleus accumbens (Borras et al 2004).…”
Section: Morphine-evoked Changes In Bold Signal Intensitysupporting
confidence: 57%
“…If at this location there was no spike activity with signal to noise ratio of at least 3:1, the electrodes were moved down in steps of about 5μm until they showed spike activity with good signal to noise ratio. Once good signal was obtained, the electrode was permanently fixed to the skull with dental acrylic cement and the second electrode in the other hemisphere was implanted in a similar way (Dafny et al, 1973, 1979, 1980, 1981, 1983; Dafny and Terkel, 1990; Yang et al, 2006b, c). The electrode leads were attached to an amphenol plug and the latter was cemented to the skull.…”
Section: Methodsmentioning
confidence: 99%
“…The different response patterns observed within each region after morphine administration were expected by the investigators; it has been previously reported [Dafny and Burks, 1976a;Dafny et al, 1979Dafny et al, , 1980Gebhart, 19821 that within a particular structure different response patterns to morphine treatment were obtained. Since "simple" agents such as acetylcholine or dopamine, as well as somatosensory stimulation, induced different response patterns within specific CNS nuclei [Bloom et al, 1965;Dafny and Feldman, 1970;Kitai et al, 19761, it was expected that a "complex" drug such as morphine would induce an even larger variety of response patterns.…”
Section: Discussionmentioning
confidence: 93%